Metode Musyafahah sebagai Solusi Mempermudah Anak Usia Dini Menghafal Surat Pendek - Nikmatus Sholihah; Nia Indah Purnamasari (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2020)
Memorizing the Qur'an is ideally applied to children from an early age, so that they are accustomed to using the time to do activities that are beneficial for their lives and future. However, the ability to memorize the Qur'an in early childhood is decreasing in quality and quantity. This is caused by several factors, one of which is an inappropriate and unattractive method for students. Therefore, the mushafahah method can be an alternative solution that is suitable and easy to implement. The purpose of this study was to find out empirical data on the application of the Musyafahah method and to analyze how much the result of the application of the Musyafahah method to facilitate early childhood memorizing short letters in group B in TK Dharma Wanita Persatuan Ngingas Waru Sidoarjo. This research is a field research with a qualitative approach. Based on the results of the study, it can be concluded that the mushafahah method can make it easier for early childhood to memorize short letters well and fluently, especially in the TK B Dharma Wanita Persatuan Ngingas Waru Sidoarjo group. In addition, the mushafahah method can provide experience for students to be able to communicate directly with the teacher, children are also more enthusiastic and more interested in memorizing.